Knowledge, attitudes, and practices of family members of children aged 2–6 years with snoring regarding pediatric snoring and its management - Zhenghan Fang; Yanxia Zhao (BMC Public Health)
Abstract Background This study aimed to explore the knowledge, attitudes, and practices (KAP) of family members of children aged 2–6 years who snore, particularly regarding prevention, treatment, and care. Methods Conducted in Shenzhen from July 20 to October 20, 2024, data were collected using structured questionnaires assessing demographics and KAP scores. Results A total of 483 valid questionnaires were analyzed, with 318 (65.84%) completed by mothers. The majority of children (164, 33.95%) were 4 years old, and 254 (52.59%) were boys; 237 (49.07%) had snored for 6–12 months. The mean knowledge, attitude, and practice scores were 9.17 ± 2.98 (range: 0–12), 21.21 ± 1.44 (range: 5–25), and 22.34 ± 3.55 (range: 6–30), respectively. Mediation analysis found that average monthly income per person (β = 0.303, P = 0.005), education or training (β = -5.334, P = 0.020), and gender (β = -0.941, P = 0.012) had significant direct effects on knowledge. Meanwhile, knowledge (β = 0.23, P = 0.011), children’s age (β = 0.157, P = 0.006), education or training (β = 0.484, P = 0.008), duration of the child had snoring (β = -0.286, P = 0.007), and education level (β = 0.785, P = 0.014) had significant direct effects on attitude. Further, knowledge (β = 0.590, P = 0.011), attitude (β = 0.428, P = 0.008), employment status (β = -1.609, P = 0.031), children’s age (β = 0.22, P = 0.037) had significant direct effects on practice. Conclusion This study highlight the crucial roles of knowledge and attitude in shaping care practices, and underscore the significant influence of demographic factors (such as income, education/training, and caregiver gender) on KAP scores. These insights suggest that targeted interventions focusing on increasing awareness and providing specific education/training are essential to improve the prevention, treatment, and care practices for childhood snoring.